2019
DOI: 10.1007/s40726-019-00125-4
|View full text |Cite
|
Sign up to set email alerts
|

How Harmful Is Particulate Matter Emitted from Biomass Burning? A Thailand Perspective

Abstract: Purpose of Review A large body of epidemiological evidence demonstrates that exposure to particulate matter (PM) is associated with increased morbidity and mortality. Many epidemiology studies have investigated the health effects of PM in Europe and North America and focussed on traffic derived PM. However, elevated levels of PM are a global problem and the impacts of other sources of PM on health should be assessed. Biomass burning can increase PM levels in urban and rural indoor and outdoor environments in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 115 publications
2
43
0
Order By: Relevance
“…Liu et al [55] found no indication of curtailed risks at higher concentrations of PM 10 for ischemic and hemorrhagic stroke hospitalisations. While toxicity studies have indicated potential differences based on the type of biomass, such detail is not widely available for epidemiological data [11]. Another possible explanation for the lack of an exposure-response effect on burning days in our study is that individuals might engage in exposure reduction activities (e.g.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Liu et al [55] found no indication of curtailed risks at higher concentrations of PM 10 for ischemic and hemorrhagic stroke hospitalisations. While toxicity studies have indicated potential differences based on the type of biomass, such detail is not widely available for epidemiological data [11]. Another possible explanation for the lack of an exposure-response effect on burning days in our study is that individuals might engage in exposure reduction activities (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…A review of the health effects of wildfire smoke identified consistent evidence of respiratory morbidity, though less clear effects on cardiovascular health [10]. An examination of both epidemiological and toxicological studies concluded that it was not yet clear if urban (traffic) and biomass-derived PM entail differential health hazards [11].…”
Section: Introductionmentioning
confidence: 99%
“…There is no consistent scientific evidence supporting this belief. Toxicological studies have consistently demonstrated that particles derived from biomass burning can activate inflammatory, oxidative and genotoxic responses, similar to road traffic particles . A recent systematic review of epidemiological studies has shown higher asthma‐related effects for PM 2.5 from landscape fire smoke compared with other sources …”
Section: Risk Communicationmentioning
confidence: 99%
“…The health effect ranges from cardiovascular, respiratory, neurocognitive and reproductive health effect. The most important one is cardiovascular and respiratory health effect [4][5][6].…”
Section: Introductionmentioning
confidence: 99%